(untitled) (European Journal of Pure and Applied Mathematics, 2017)
The aim of this work is to show the existence of weak solutions and supersolutions forÂ a nonlinear system modelling Ions migration through biological cells membranes with L1- Data. InÂ the first step, we describe the mathematical model after that we define an approximating scheme. Under simplifying assumptions on the model equation, we prove some L1 a priori estimates, thenÂ we prove that the solution of the truncated system converges to the solution of our main problem.